Effect of nano-selenium on the activities of glutathione peroxidase and type- I deiodinase in liver of avian broiler chicks - XU Bao-hua; Hu Cai-hong; XIA Mei-sheng (浙江大学学报. 农业与生命科学版)
Avian broiler chicks, 1 d of age, were used to investigate the effects of nano elemental selenium (nano-Se) or sodium selenite (Na2SeO3) on the activities of glutathione peroxidase and type-Ⅰdeiodinase in liver. The chicks were allocated to 11 treatments, each of which had 3 pens of 45 chicks per pen. The eleven dietary treatments were basal diet only (containing 0.040 mg/kg Se) and basal diet +0.10, 0.20, 0.30, 0.40 or 0.50 mg/kg Se as Na2SeO3 or nano-Se. The results were as follows: (i) When Na2SeO3 was added to the diet, the growth performance and GSH-Px activities in liver of chicks increased with the increase in Se within the Se concentration range of 0-0.20 mg/kg and remained steady at the peak value within the within the range of 0.20-0.40 mg/kg. (ii) Supplement of 0.50 mg/kg Se as Na2SeO3 to the diet reduced (P<0.05) growth performance and GSH-Px activities as compared with the addition of Se at a concentration range of 0.20-0.40 mg/kg. With addition of nano-Se, the growth performance and GSH-Px activities remained steady at the peak value even at a concentration of 0.50 mg/kg Se. (iii) There were no difference in growth performance between the treatments of nano-Se and Na2SeO3 when the added concentration of Se was within 0.10-0.40 mg/kg. The chicks had higher (P<0.05) growth performance and GSH-Px at a concentration of 0.50 mg/kg as nano-Se than Na2 SeO3. (iv) Supplementation with Se increased the activity of type-I deiodinase in liver. The extent of increase was, however, not affected by source of Se and the concentration of Se added. The results implicated that the optimal Se concentration range on the Weinberg curve for nano-Se is wider than that for Na2 SeO3.